Assessment of typing methods, virulence genes profile and antimicrobial susceptibility for clinical isolates of Proteus mirabilis - Lamiaa A. Salama; Hazem Hamed Saleh; Shaymaa H. Abdel-Rhman; Rasha Barwa; Ramadan Hassan (Annals of Clinical Microbiology and Antimicrobials)
Abstract Proteus mirabilis (P. mirabilis) is one of the most important causative pathogens associated with complicated urinary tract infections with a 20% incidence. For epidemiological determinations, several phenotypic and molecular typing methods have been implicated. Sixty P. mirabilis isolated undergo antibiotic susceptibility test by standard Kirby Bauer method. They showed high resistance to nitrofurantoin and trimethoprim/sulfamethoxazole that appear mainly in 3rd age group. The 2nd age group comprised most of the resistant isolates to the tested antibiotics. A total of 73.33% of isolates were classified as multi drug resistance (MDR) and 78.3% of isolates were distributed in several antibiotypes with MAR index over 0.2. Twenty-one isolates were strong biofilm-producers and they were significantly related to MDR. Different virulence factors as protease, urease and hemolysin production are detected. Detection of several virulence genes by PCR; zapA and ureC were harbored by all isolates, followed by rsbA (95%), ureA and flaA (93%), hpmA (91.7%) and mrpA (73.3%). Determination of genetic diversity between isolates was performed by different methods (RAPD, ISSR, ERIC, BOX-AIR and REP-PCR) by using several parameters as typeability and discriminatory power indicating that ERIC-PCR was the best method followed by REP-PCR 1R. Rand’s & Wallace coefficients were used for calculating the congruence among typing methods. Conclusions: The results obtained from both conventional and molecular typing methods indicated that molecular methods are superior to conventional methods in the discrimination of isolates. ERIC-PCR and Rep-PCR provide high discrimination ability among P. mirabilis clinical isolates contributing to epidemiological studies.